2010
DOI: 10.1002/0471143030.cb1412s48
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Arf GTP‐Binding Protein Function in Cells

Abstract: This unit describes techniques and approaches that can be used to study the functions of the ADP‐ribosylation factor (Arf) GTP‐binding proteins in cells. There are six mammalian Arfs and many more Arf‐like proteins (Arls), and these proteins are conserved in eukaryotes from yeast to humans. Like all GTPases, Arfs cycle between GDP‐bound, inactive and GTP‐bound active conformations, facilitated by guanine nucleotide exchange factors (GEFs) and GTPase‐activating proteins (GAPs) that catalyze GTP binding and hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 15 publications
3
23
0
Order By: Relevance
“…S7A), but Arf1 activity remained elevated, vesicle uncoating was impaired, trafficking was delayed and Golgi ribbons were dispersed. Activation of Gi and release of ‘free’ Gβγ dimers is also a central mechanism by which GIV terminates Arf1 at/near acceptor (i.e., Golgi) membranes, and is consistent with prior work demonstrating the inhibitory role of Gβγ in Arf signaling (Cohen and Donaldson, 2010; Colombo et al, 1995). Although hierarchically dominant, the GIV→Gβγ pathway is dependent on the GIV→ArfGAP2/3 pathway, because the ability of GIV-GEF to downregulate Arf1 activity is abolished in cells without ArfGAP3 (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…S7A), but Arf1 activity remained elevated, vesicle uncoating was impaired, trafficking was delayed and Golgi ribbons were dispersed. Activation of Gi and release of ‘free’ Gβγ dimers is also a central mechanism by which GIV terminates Arf1 at/near acceptor (i.e., Golgi) membranes, and is consistent with prior work demonstrating the inhibitory role of Gβγ in Arf signaling (Cohen and Donaldson, 2010; Colombo et al, 1995). Although hierarchically dominant, the GIV→Gβγ pathway is dependent on the GIV→ArfGAP2/3 pathway, because the ability of GIV-GEF to downregulate Arf1 activity is abolished in cells without ArfGAP3 (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…To determine if GIV or its GEF function modulate Arf1 activity in cells, we used the previously validated pull-down assay with a GST-GAT domain of GGA3 which selectively binds the active GTP-bound pool of Arf1 (Cohen and Donaldson, 2010). We found that compared to control cells, the levels of Arf1•GTP were increased ~60% in GIV-depleted cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That GIV terminates Arf1 at/near acceptor (i.e. Golgi) membranes via release of free Gbg is consistent with prior work demonstrating the inhibitory role of Gbg in Arf signaling [78,79]. Thus, this work elucidated some of poorly understood functions of G proteins on the Golgi and illuminated the role of trimeric G protein signaling in the secretory pathway.…”
Section: Giv Regulates Secretion By Activating Gai On Golgi Membranessupporting
confidence: 86%
“…ARF activity was measured using an ARF pull-down assay essentially as described earlier 70 . GST-VHS-GAT (VHS-GAT from GGA3) was bacterially expressed, and the cell pellet spun down at 4000 rpm −1 .…”
Section: Methodsmentioning
confidence: 99%